The Selection, Use, and Content of Picture Books about Issues of Race in Early Elementary School - Felsinger, Kathryn Yvonne (Mills College, 2018)
The purpose of this study was to investigate the selection and use of picture books about issues of race by an early elementary school teacher, and to critically examine the content of selected picture books about race. The research questions were: How does a self-identifying anti-racist transitional kindergarten teacher in a public elementary school select and utilize children’s picture books to address issues of race with their students? What are the underlying messages about race in the books? The case study utilized Seidman’s (2013) three-interview series and critical content analysis was used to analyze ten selected picture books. The case study findings revealed that the personal identity and experiences of the participant and her relationship with her students and their families shape her professional race-related goals. Further findings demonstrated that the participant uses picture books to teach about race for a variety of reasons, including that they make race, an abstract concept, concrete for her students. The critical content analysis revealed that the race and experiences of the author or illustrator informed the content and underlying messages in the books. The results of this study add new dimensions to the field’s understanding of what factors inform a teacher’s selection and use of picture books about race, and what themes are common in children’s picture books that address the topic of race. Additionally, this study demonstrates the need for books written and illustrated by people of color in order to provide young children with more authentic representations of the lives and experiences of racially and culturally diverse people.